Microcosmic thermal analysis of coal mixed with oxides at different temperatures. (2018) - Huang, Chung-Fu; Huang, An-Chi; Zhao, Jing-Yu; Deng, Jun; Shu, Chi-Min; Wan, Terng-Jou
Disaster prevention in multiple mining is an area of research focus worldwide. Although coal is the most abundant and cheapest energy resource, its disadvantages cannot be ignored. In particular, spontaneous combustion events in mines have been regularly reported. Therefore, the factors responsible for these disasters must be identified and preventive measures implemented. The objective of the present study was to establish a mechanism for the thermal stability analysis of lignite and long flame coal mixed with CuO, Fe2 O3, or coal's products; the mechanism involves conducting thermogravimetric analyses at different temperatures. The kinetic parameters obtained through these analyses facilitate the development of remining technology and the improvement of standard operating processes in remining. Moreover, they contributed to the safer design of instruments and the development of a database on the risk of spontaneous coal fires. [Received: November 25, 2016; Accepted: March 12, 2017]